Differential flow improvements after valve replacements in bicuspid aortic valve disease: a cardiovascular magnetic resonance assessment - Bissell, Malenka M.; Loudon, Margaret; Hess, Aaron T.; Stoll, Victoria; Orchard, Elizabeth; Neubauer, Stefan; Myerson, Saul G. (Journal of cardiovascular magnetic resonance, 2018)
Background Abnormal aortic flow patterns in bicuspid aortic valve disease (BAV) may be partly responsible for the associated aortic dilation. Aortic valve replacement (AVR) may normalize flow patterns and potentially slow the concomitant aortic dilation. We therefore sought to examine differences in flow patterns post AVR. Methods Ninety participants underwent 4D flow cardiovascular magnetic resonance: 30 BAV patients with prior AVR (11 mechanical, 10 bioprosthetic, 9 Ross procedure), 30 BAV patients with a native aortic valve and 30 healthy subjects. Results The majority of subjects with mechanical AVR or Ross showed normal flow pattern (73% and 67% respectively) with near normal rotational flow values (7.2 ± 3.9 and 10.6 ± 10.5 mm 2 /ms respectively vs 3.8 ± 3.1 mm 2 /s for healthy subjects; both p > 0.05); and reduced in-plane wall shear stress (0.19 ± 0.13 N/m 2 for mechanical AVR vs. 0.40 ± 0.28 N/m 2 for native BAV, p < 0.05). In contrast, all subjects with a bioprosthetic AVR had abnormal flow patterns (mainly marked right-handed helical flow), with comparable rotational flow values to native BAV (20.7 ± 8.8 mm 2 /ms and 26.6 ± 16.6 mm 2 /ms respectively, p > 0.05), and a similar pattern for wall shear stress. Data before and after AVR ( n = 16) supported these findings: mechanical AVR showed a significant reduction in rotational flow (30.4 ± 16.3 → 7.3 ± 4.1 mm 2 /ms; p < 0.05) and in-plane wall shear stress (0.47 ± 0.20 → 0.20 ± 0.13 N/m 2 ; p < 0.05), whereas these parameters remained similar in the bioprosthetic AVR group. Conclusions Abnormal flow patterns in BAV disease tend to normalize after mechanical AVR or Ross procedure, in contrast to the remnant abnormal flow pattern after bioprosthetic AVR. This may in part explain different aortic growth rates post AVR in BAV observed in the literature, but requires confirmation in a prospective study.